Tending the Soil: How to Grow a Successful Faculty Peer-Mentoring Group - Hudson, Jennifer (Academic Leader, 2026)
When a new faculty member is hired at a university, having trusted colleagues and faculty mentors who help navigate a path to growth, belonging, and success is essential.
Keywords: dept.aa

Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Not all fun and games: videogame labour, project-based workplaces, and the new citizenship at work - Milburn, Trudy (Journal of Broadcasting & Electronic Media, 2025)
Keywords: Citizenship; Engineering; Law; Political science; Public relations; Sociology; Work (physics); dept.aa

Considering the moment: Workforce development for the faculty–administrator transition - Milburn, Trudy; Winchatz, Michaela (Communication Education, 2026)
Keywords: Higher education; Job training; Transition (genetics); Transition countries; Workforce; Workforce development; dept.aa

Book Review: Culture 2.0: The Intersection of National and Organizational Culture and Unruly Speech: Displacement and the Politics of Transgression - Milburn, Trudy (Management Communication Quarterly, 2024)
Keywords: book review; dept.aa

Sword with a dual edge: Membership categorization and stereotyping in elite European club football commentary (chapter 12) - Hansen, Alan; Milburn, Trudy (Communicated Stereotypes at Work, 2024)
Communicated Stereotypes at Work highlights the pervasiveness and complexity of stereotypes in the workplace by analyzing the role they play in a variety of professional settings. Contributors exp...
Keywords: dept.aa

Organizational communication scholars and U.S. higher education leadership: opportunities and challenges when scholars become administrators - Castor, Theresa; Milburn, Trudy; Eisenberg, Eric M.; Shockley-Zalabak, Pam (Management Communication Quarterly, 2025)
Universities and colleges are organizations that significantly impact students, their communities, and society. This forum explores how organizational communication scholars who are university leaders have applied their scholarly backgrounds to inform their roles. The forum participants engage in the work of being reflective practitioners to shed light on how organizational communication theory can help in negotiating the everyday lived experience of academic leadership. Three key issues are explored: (1) in what ways are organizational communication scholars uniquely positioned to assume a university leadership role? (2) how do communication concepts inform the communication practices of administrators? and (3) how do communication practices contribute to universities as multi-faceted institutions? The participants conclude by reflecting on current challenges in higher education and the potential of organizational communication scholars to play a vital role in navigating those challenges.
Keywords: dept.aa; peer-reviewed

Cultural discourse analysis: discourse hubs as heuristic devices - Carbaugh, D.; Milburn, T.; Scollo, M.; van Over, B. (The Routledge Handbook of Cultural Discourse Studies, 2024)
The purpose of this chapter is twofold; we first review our approach to cultural discourse analysis and then explicate the role of “discursive hubs” within it. The six discursive hubs we discuss are A Hub of Being: How is identity expressed? Acting: How do we express what we are doing? Relating: How do we express that we are related to each other? Feeling: How do we express what we feel? Dwelling: How do we express where we are (place) in our natural world (or material environment)? Timing: How do we express the understanding of process or sequencing over time? Our chapter brings to the fore several features of the general construct, discursive hub. Each feature of a hub adds an essential aspect to studies of cultural discourses. The set of features offers a systematic guideline for the design and execution of cultural discourse analytic studies into discursive hubs. Specifically, the set of features includes (a) The research question each hub raises; (b) the specific bits of discourse each concept of “discourse hub” makes relevant; (c) the socio-cultural functions of each hub within discourses or what that hub does within a discourse and (d) symbolic instantiations of that hub (in language, images, sounds and other signs) in actual cases of cultural discourse. Our discussion of the discourse hubs then turns to the heuristic role they play in the conduct of cultural discourse analyses. We emphasise that the hubs often work deeply together and thus their interrelationships breathe social life into cultural discourses. © 2024 selection and editorial matter, Shi-xu; individual chapters, the contributors.
Keywords: dept.aa

Engaging and transforming global communication through cultural discourse analysis: a tribute to Donal Carbaugh - Scollo, Michelle; Milburn, Tracy (2023)
The book is a handbook of cultural discourse analysis, a theory developed by Donal Carbaugh, and celebration of his work. The book features an explanation of the theory and sixteen chapters using ...
Keywords: dept.aa

Brief Report: A Specialized Fitness Program for Individuals with Autism Spectrum Disorder Benefits Physical, Behavioral, and Emotional Outcomes - Jackson, S.L.J.; Abel, E.A.; Reimer, S.; McPartland, J.C. (Journal of Autism and Developmental Disorders, 2022)
Individuals with autism spectrum disorder (ASD) engage in less physical activity than typically-developing peers. This can result in serious negative consequences for individual well-being and may contribute to the physical, behavioral, and emotional challenges associated with ASD. This study explored the potential benefits of trainer-led, individualized, physical fitness sessions specialized for ASD. Eleven individuals (ages 7–24 years) with ASD were assessed at baseline and following 15 fitness sessions. Participants demonstrated improvements in core and lower-body strength and reductions in restricted and repetitive patterns of behavior, along with non-significant but marked reductions in issues with daytime sleepiness. Results suggest the merit of specialized fitness programs and emphasize the need for larger and more rigorous research studies on this topic. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
3 citations (Crossref) [2023-10-31]
Keywords: Autism spectrum disorder; Exercise; Fitness; Physical health; Restricted and repetitive behaviors; Sleep behaviors; dept.aa; dept.adm; peer-reviewed

New England Town Meeting and the Cultivation of Deliberative Play - Townsend, Rebecca M.; Milburn, Trudy (American Behavioral Scientist, 2022)
Participants of New England town meeting must follow protocols to participate in this direct democratic process. Over the past 200 years, the protocols have been enacted and adapted by participants in small towns across the region. Within annual meetings, one can find small breaches that could be interpreted as playful acts. In this paper, we use the comic frame as a theoretical lens to interpret instances of such play within the rhetorical deliberation of one New England town meeting. We analyze two instances where speakers playfully use recognized parts of town meeting to achieve their rhetorical ends. We conclude with a discussion of the way play can help accomplish identification in public discourse.
1 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed

The emotional effects of literacy: Vietnamese women negotiating the shift to a market economy - Crawford, I.W. (Women and Lit.: Local and Glob. Inq. for a New Century, 2020)
Journal Abbreviation: Women and Lit.: Local and Glob. Inq. for a New Century
Keywords: dept.aa

Coded communities: organizing boundless diversity - Milburn, Trudy A. (Annals of the International Communication Association, 2021)
Communication researchers have used speech codes theory to interpret local conduct. This qualitative meta-analysis draws upon twenty years of peer-reviewed journal articles and books (2000–2019) that specifically use the concept of speech community within research about speech codes. Although speech community is incorporated into one of the six main tenets of speech codes theory, the concept has not been used consistently. After reviewing how speech codes theory researchers use the concept of speech community, I draw comparisons between those who describe mediated and intercultural practices to interrogate the a priori assertion of a speech community. I conclude by arguing that one must understand the particular social relations among speakers before asserting the existence of a speech community. © 2021 International Communication Association.
2 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed; ⛔ No DOI found

Core dimensions of autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L.J. (New Oxford Textbook of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests during the early developmental period of childhood. Behaviourally characterized by impairments in social interaction and communication, in combination with stereotyped and restricted patterns of behaviour and/or interest, it is currently believed that ASD occurs in approximately 1–2% of individuals. ASD is more prevalent among males than females (4–5:1), but the mechanisms resulting in this discrepancy are still unclear. This chapter will serve as an introduction to ASD, covering the topics of disorder history, prevalence rates, demographics, diagnostic criteria, differential diagnosis, and discussions on current and future diagnostic classification systems. The remaining chapters within Section 4 will then provide detailed discussions on more specific topics related to ASD, including current understandings of treatment planning, prevention and epidemiology, genetics, imaging, and disorder management.
tex.ids: volkmarCoreDimensionsAutism2020a
Keywords: dept.sed